Front cover: Alternating or continuous exposure to cafeteria diet leads to similar shifts in gut microbiota compared to chow diet. Issue 1 (January 2017) - Kaakoush, Nadeem O.; Martire, Sarah I.; Raipuria, Mukesh; Mitchell, Hazel M.; Nielsen, Shaun; Westbrook, R. Fred; Morris, Margaret J.
Abstract : Mol. Nutr. Food Res . 2017, 61, 1500815. DOI:10.1002/mnfr.201500815 Rats either continuously fed chow or Western‐style cafeteria diet are compared to a "cycled" group switched between the two diets over 16 weeks. Cafeteria rats weigh 36% and cycled rats 18% more than controls, with metabolic parameters intermediate between the other groups. The gut microbiota of cycled rats is nearly indistinguishable from rats under constant cafeteria diet, and both groups are significantly different to the chow group. Artwork by Shyam Prakaash Bhagavata.